The Relationship Between Arm Muscle Strength and Anaerobic Endurance and the 20-Meter Whitewater Rafting Boat Time Trial - Farhan Shafrizal; Iwan Hermawan; Dinan Mitsalina M.Or (The Future of Education Journal, 2026)
This study aims to examine the relationship between arm muscle strength and anaerobic endurance and rafting boat completion time over a distance of 20 meters. The study employed a quantitative descriptive method with an associative approach. The sample consisted of 12 R4-category rafting athletes aged 16–19 years who were selected using purposive sampling. The instruments used included the Dynox Dynamometer Pull to measure arm muscle strength, the Running-Based Anaerobic Sprint Test (RAST) to measure anaerobic endurance, and a 20-meter rafting boat completion time test using a stopwatch, with each athlete given two trials. The normality test results indicated that arm muscle strength and anaerobic endurance were normally distributed, whereas rafting boat completion time was not normally distributed. Therefore, the data were analyzed using the non-parametric Spearman rank correlation test. The results showed a positive relationship between arm muscle strength and rafting boat completion time (r = 0.355), as well as between anaerobic endurance and rafting boat completion time (r = 0.237); however, neither relationship was statistically significant (p > 0.05). The study concludes that arm muscle strength and anaerobic endurance do not have significant relationships with rafting boat completion time over a distance of 20 meters. This finding suggests that rafting boat completion time may be influenced more strongly by other factors, such as paddling technique, team coordination, and environmental conditions.